Russia’s military conflict against Ukraine and its impact on the European Union’s wealth. Can good governance counteract the effects of the war? - Camelia Negri; Gheorghiţa Dincă (Frontiers in Environmental Science, 2023)
Russia’s war against Ukraine, which originated in the midst of the COVID-19 pandemic, is undoubtedly one of the defining events of this current period, expected to exert a significant impact on the entire world’s economies. This study aims to determine whether the conflict between Russia and Ukraine has a significant impact on European Union (EU) Member States, particularly on the economic output of the EU countries, in the post-pandemic context. Difference-in-difference methodology alongside panel data econometric techniques are used to study the relationship between the effects of war, reflected in the deepening energy crisis, inflation, limited trade relations, restructuring of governmental expenditures, and the migrant crisis, together with economic freedom and governance quality as elements of neoliberal doctrine, and the economic wealth of EU Member States for the 1995–2021 period. In light of current research, the results prove that war has a significant impact on the economic output of the European Union structure, especially for the EU countries that rely the most on Russia’s energy imports. Using the difference in difference analysis, the impact of war on gdp_cap is evaluated as a drop in economic output of −405.08 euros per capita in the considered European countries. Applying panel regression analysis, defense and military expenditures, inflation, lack of trade openness, and increased levels of energy dependence negatively impact economic growth in the EU economies. In addition, this study provides essential information for public officials in order to prepare the EU economy for the recovery from war shocks in the forthcoming period, taking into account the study’s policy recommendations regarding energy reliance, restructuring public expenditure, prioritizing investment, and improving governance quality.